REDUCING LABOR PAIN WITH WARM COMPRESS ON THE 1ST STAGE LABOR OF ACTIVE LABOR PHASE - Talitha Aslamiyah; Gatut Hardiato; Kating Kasiati (Universitas Airlangga, 2021)
Abstract Background: Labor pain is a visceral nociceptive pain caused by contraction and dilatation of the cervix. This condition affects the mother physically and psychologically. Pain that cannot be handled alone will cause anxiety and stress. Various techniques have been used to reduce pain during labor, which reduce emotional stress, increase calm, and physical contact while reducing pain. Warm compresses are a non-pharmacological method that can reduce labor pain. In addition, warm compresses are also a method that is cheap, simple, safe, and effective, without adverse side effects, and in accordance with the competence of midwives. This study aims to determine the effect of warm compresses in the first stage of the active phase on reducing labor pain. Methods: This research method is pre experimental designs with one group pretest-posttest research design. The number of samples as many as 10 maternity with purposive sampling sampling technique. This research was conducted in September-October 2019. Data analysis used the dependent T test. Results: The results showed that based on the results of the dependent t-Test test, the p value / Sig. (2-tailed) of 0.005, <0.05, thus there is a significant (significant) decrease between the average labor pain before which is 8.12 and after warm compresses is 6.86. Thus, there is an effect of warm compresses during the first stage of the active phase on reducing labor pain. Conclusion: There is an effect of warm compresses on decreasing labor pain scale.